Detecting topological phase transitions in a double kicked quantum rotor - Bolik, Nikolai; Groiseau, Caspar; Clark, Jerry H.; Summy, Gil S.; Liu, Yingmei; Wimberger, Sandro (Physical review, 2022)
We present a concrete theoretical proposal for detecting topological phase transitions in double kicked atom-optics kicked rotors with internal spin-1/2 degree of freedom. The implementation utilizes a kicked Bose-Einstein condensate evolving in one-dimensional momentum space. To reduce the influence of atom loss and phase decoherence, we aim to keep experimental durations short while maintaining a resonant experimental protocol. Experimental limitations induced by phase noise, quasimomentum distributions, symmetries, and the ac-Stark shift are considered. Our results thus suggest a feasible and optimized procedure for observing topological phase transitions in quantum kicked rotors.